Characterising and comparing the sleep characteristics and behaviours of female and male soccer players: A cross-sectional survey of an elite soccer club - Sanders, N.; Randell, R. K.; Thomas, C.; Bailey, S. J.; Clifford, T. (Sports, 2025)
The aim of this cross-sectional study was to evaluate the sleep characteristics and behaviours of senior male, senior female, and under 21 (U21) male elite soccer players using athlete-specific questionnaires. During the preseason/early season period, 74 players from the English Premier League (n = 26, age 26 ± 5 y), Women`s Super League (n = 22, age 25 ± 5 y), and English Premier League 2 (n = 26, age 19 ± 1 y) completed the validated Athlete Sleep Screening Questionnaire (ASSQ) to obtain a sleep difficulty score (SDS) and the Athlete Sleep Behaviour Questionnaire (ASBQ) to obtain a global score and individual behaviours. We found that sleep difficulty scores were higher in senior females (5.9 ± 1.9) than senior males (4.1 ± 1.7) and U21 males (4.3 ± 1.2) (p = 0.006), but no severe clinical problems were noted. Global sleep behaviour scores from the ASBQ were worse in senior males (37.9 ± 6.5) and senior females (40.6 ± 7.1) than male U21 players (33.6 ± 4.7) (p = 0.021). Senior players consumed more alcohol and stimulants and felt that travel disrupted sleep; females went to bed thirstier, woke more for the bathroom, and ruminated more prior to sleep (all p < 0.05). In conclusion, senior female players reported more sleep difficulties than male senior and male U21 players. Behaviours such as pre-bed rumination, nutrition, and travel plans could be targeted to improve sleep quality in soccer players. Study limitations include data drawn from a single club in the off-season.